Pengaruh Lifestyle Konsumen Terhadap Keputusan Membeli Produk - Runik Puji Rahayu; Alfi Hasaniyah; Faizal Aprileo (Yos Soedarso Economic Journal (YEJ), 2020)
To find out consumer tastes, searches are often done so that consumers know the behavior and tastes that are increasingly dynamic and constantly changing. Dynamic environmental changes cause consumer lifestyle studies that are identified by how people spend their time (activities) can be seen from their style of speaking, style of dress and also their friends or teenage relationships. Then what they consider important in their environment (interest) that can be seen from hobbies, fun, or entertainment. As well as what they think about themselves and the world around them (opinions) can be seen from maintaining the image or self-esteem. The purpose of the study was to determine whether the effect of activity, interest and opinion variables had an effect simultaneously on the decision to buy Friday Killer Pamekasan products. This study uses quantitative methods. The population in this study is the entire community in Pamekasan. The sample used is random sampling, where the sample is taken randomly, regardless of the level in the population, each element of the population has the same opportunity and is known to be selected as an object. The number of samples used in this study is 100 respondents while the data analysis technique used is multiple linear regression analysis. Based on multiple linear regression analysis stated that variable lifestyle consisting of activities, interests, and opinions, simultaneously influence the decision to buy Friday Killer Pamekasan products. Activity variables have a more dominant influence between interests and opinions on the decision to buy Pamekasan Distro Friday Killer products.Â Keywords: Lifestyle; Activities; Interests; Opinions; Purchasing Decisions